2017
DOI: 10.1136/jramc-2017-000822
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the health risks of help-seeking military veterans living in different parts of the UK

Abstract: The findings from this paper suggest that a greater focus needs to be placed on treating physical problems in Northern Irish veterans. Alcohol misuse should be addressed in more detail in treatment programmes, particularly in Scotland and Wales. As few differences were found in the mental health presentations, this suggests that standardised services are adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Veterans completing this survey may not be representative of all treatment-seeking veterans in the UK and may differ from veterans seeking treatment from other mental health services. However, given that CS has a nationwide presence, receives approximately 2500 referrals each year23 and is an NHS-recognised treatment pathway for veteran mental health problems,13 the study’s results are likely to have reasonable validity. Second, a small number of female participants means that the results can only be generalised to treatment-seeking male veterans.…”
Section: Discussionmentioning
confidence: 94%
“…Veterans completing this survey may not be representative of all treatment-seeking veterans in the UK and may differ from veterans seeking treatment from other mental health services. However, given that CS has a nationwide presence, receives approximately 2500 referrals each year23 and is an NHS-recognised treatment pathway for veteran mental health problems,13 the study’s results are likely to have reasonable validity. Second, a small number of female participants means that the results can only be generalised to treatment-seeking male veterans.…”
Section: Discussionmentioning
confidence: 94%
“…Treatment-seeking veterans endorsed exposure to a greater number of adverse childhood experiences than the wider military population 24 26. While the majority of the veterans sampled lived in England, comparison to the Royal British Legion’s most recent household survey showed that there was a higher proportion of veterans residing in Scotland, Wales and Northern Ireland seeking support for mental health difficulties than might be expected from the distribution of veterans around the UK 27. Compared with participants who resided in England, those living in Northern Ireland tended to be older and have more physical health needs, and those living in Wales and Scotland reported higher rates of alcohol problems and increased risk of living in areas of deprivation 27 28.…”
Section: Introductionmentioning
confidence: 93%
“…The paper in the current issue of JRAMC explored differences in health presentations between veterans residing in the different nations in the UK 20. There seems to be little difference between the mental health presentations, but veterans residing in Scotland and Wales were at increased risk of alcohol misuse and those residing in Northern Ireland were older and reported significantly more physical health difficulties.…”
Section: Presentations Of Help-seeking Veteransmentioning
confidence: 99%